Impacts of sodium butyrate on intestinal mucosal barrier and intestinal microbial community in a weaned piglet model - Liu, Han; Zhao, Jing; Zhang, Wenju; Nie, Cunxi (Frontiers in Microbiology, 2023)
Butyrate is thought to enhance intestinal mucosal homeostasis, but the detailed mechanism remains unclear. Therefore, to further elucidate the mechanism of butyrate regulation of intestinal mucosal homeostasis, this study used weaned piglets with similar intestinal metabolic function to humans as a research model. The dietary supplemented 0.2% sodium butyrate group (0.2% S) and negative control group (CON) were established to detect the effects of butyrate on growth performance, intestinal tissue morphology, mucosal barrier function, and intestinal microbial community structure of weaned piglets. Results showed that there was an increase in average daily gain (ADG) during three different experimental periods and a reduction in average daily feed intake (ADFI) and feed to gain ratio (F:G) during days 1–35 and days 15–35 in 0.2% S compared with CON (P > 0.05). Furthermore, villus height in the ileum and duodenum were increased and crypt depths in the colon and jejunum were reduced in both groups (P < 0.05). Moreover, the ratio of villus height and crypt depth (V/C) in 0.2% S both in the ileum and jejunum were significantly increased (P < 0.05) compared with CON. The relative mRNA expression of PKC, MUC1, CLDN1, and ITGB1 in the ileum of 0.2% S were up-regulated compared with CON (P < 0.05). The digesta samples of 0.2% S, both in the ileum (P < 0.05) and colon, contained greater intestinal bacterial abundance and diversity of probiotics, including Lactobacillus, Streptococcus, Megasphaera, and Blautia, which promoted amino acid metabolism and energy production and conversion in the colon, and the synthesis of carbon-containing biomolecules in the ileum. In summary, dietary supplementation of 0.2% sodium butyrate was shown to have a tendency to improve the growth performance of weaned piglets and to enhance intestinal mucosal barrier function via altering the gut microbiota.